2020
DOI: 10.1177/0300060520944310
|View full text |Cite
|
Sign up to set email alerts
|

Combination of pegylated liposomal doxorubicin and docetaxel as neoadjuvant therapy for breast cancer with axillary lymph node metastasis

Abstract: Objective To evaluate the efficacy and safety of the combination of pegylated liposomal doxorubicin and docetaxel as neoadjuvant therapy for breast cancer (BC) in patients with axillary lymph node metastasis. Methods In this single-arm study, 91 patients with clinical stage IIA–IIIc breast cancer received six cycles of pegylated liposomal doxorubicin plus docetaxel as neoadjuvant chemotherapy (NAC). Trastuzumab was allowed for patients with human epidermal growth factor receptor 2-positive tumors. The primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
(130 reference statements)
1
1
0
Order By: Relevance
“…In this trial, PLD had a favourable safety profile, comparable to the one previously reported in other studies [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. In particular, in a phase II preoperative trial, treatment with PLD 20 mg/m 2 given biweekly for eight courses in combination with metronomic cyclophosphamide 50 mg/day orally was well tolerated, with no grade 4 toxicities and with grade 3 skin toxicity in three patients and hand-foot syndrome in four patients [ 20 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In this trial, PLD had a favourable safety profile, comparable to the one previously reported in other studies [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. In particular, in a phase II preoperative trial, treatment with PLD 20 mg/m 2 given biweekly for eight courses in combination with metronomic cyclophosphamide 50 mg/day orally was well tolerated, with no grade 4 toxicities and with grade 3 skin toxicity in three patients and hand-foot syndrome in four patients [ 20 ].…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, PLD has been shown to be effective and well tolerated as neoadjuvant CT for patients with locally advanced breast cancer [ 13 , 14 ]. Studies that used a combination of PLD with other agents (e.g., taxanes, gemcitabine, cisplatin, and fluorouracil) obtained a clinical response rate that ranged from 71% to 89% [ 15 , 16 , 17 , 18 , 19 ]. In a phase II trial, in 29 patients with locally advanced breast cancer who were not suitable to receive a standard chemotherapy due to age or comorbidities or who asked for a regimen with low incidence of toxic effects irrespective of age, PLD 20 mg/m 2 biweekly for eight courses was combined with oral metronomic cyclophosphamide 50 mg/day.…”
Section: Introductionmentioning
confidence: 99%